Uporaba stabilnih izotopov kisika in vodika v hidroloških raziskavah - slovenske izkušnje - Bezak, Nejc (Acta hydrotechnica, 2017)
By using stable oxygen and hydrogen isotopes in hydrological studies one can obtain answers to questions that are difficult to answer with standard hydrological measurements. For example, with stable isotopes we can determine where the water goes when it rains and identify the flow paths of rainfall to the streams. This paper shows theoretical background of stable isotopes applications in hydrological studies and connection with some of the hydrological processes such as (sub)surface runoff generation. We give a short overview of previous studies (focusing on the last 15 years) that used stable isotopes with an emphasis on studies in Slovenia. In the last part of the paper some preliminary results of an ongoing research project are presented. This project will focus on the hydrological response of the nonhomogeneous Ljubljanica catchment with the aim to enhance the knowledge about hydrological processes using stable isotopes.
Keywords: field measurements; hidrologija; hidrološki procesi; hydrological processes; hydrology; Ljubljanica catchment; porečje Ljubljanice; stabilni izotopi; stable isotopes; terenske meritve; vodni krog; water cycle